Better a Friend Nearby Than a Brother Far Away? The Health Implications of Foreign Domestic Workers' Family and Friendship Networks. (May 2020) - Ye, Jing; Chen, Feinian
Migrant domestic workers provide essential services to the families they live with, but they are not considered a part of the family. As a group, they are not well-integrated into the society and often suffer from social isolation. In this article, we explore the potential health buffering effects of their personal network, in terms of family and friendship ties in both the local community and their home country. Existing literature provides inconsistent evidence on who and what matters more, with regard to the nature, strength, and geographic locations of individual personal networks. Using data from the Survey of Migrant domestic Workers in Hong Kong (2017), we find that family ties are extremely important. The presence of family members in Hong Kong as well as daily contact with family, regardless of location, are associated with better self-reported health. Only daily contact with friends in Hong Kong, not with friends in other countries, promotes better health. We also find evidence that the protective effects of family and friends networks depend on each other. Those foreign domestic workers with families in Hong Kong but also maintain daily contact with friends have the best self-reported health among all.